1988
DOI: 10.3109/10731198809132579
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the in Vitro Stability of Artificial Red Blood Cells Based on Hemoglobin-Containing Liposomes

Abstract: The effects of membrane phospholipid composition, surface charge and cholesterol content on the deteriorating interactions between hemoglobin (Hb) and phospholipid bilayers were studied. Hb was either encapsulated in multilamellar liposomes (hemosomes), or incubated with small unilamellar vesicles (SUV). Negatively charged phospholipids increased the rate of oxyHb decay in unsaturated lipid hemosomes. This effect was not linked to Hb-induced lipid peroxidation, since the latter process was inhibited in hemosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Its purpose is to reduce membrane permeability, improve liposome resistance to fusion and lysis, hinder Hb oxidation and denaturation, and reduce lipid peroxidation. The rigid cholesterol molecule inhibits both hydrophobic- and ionic-type interactions of phospholipid membranes with proteins, probably through changes in membrane fluidity, in line with cholesterol's condensing/stabilizing effect in unsaturated bilayers. , It reduces intercalation of Hb into the lipidic bilayer and displacement of heme . The presence of cholesterol in the formulation also prevents redistribution of cholesterol from RBC membranes to the liposome membrane, a process which renders RBCs osmotically fragile …”
Section: Phospholipids and Liposome Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Its purpose is to reduce membrane permeability, improve liposome resistance to fusion and lysis, hinder Hb oxidation and denaturation, and reduce lipid peroxidation. The rigid cholesterol molecule inhibits both hydrophobic- and ionic-type interactions of phospholipid membranes with proteins, probably through changes in membrane fluidity, in line with cholesterol's condensing/stabilizing effect in unsaturated bilayers. , It reduces intercalation of Hb into the lipidic bilayer and displacement of heme . The presence of cholesterol in the formulation also prevents redistribution of cholesterol from RBC membranes to the liposome membrane, a process which renders RBCs osmotically fragile …”
Section: Phospholipids and Liposome Formulationmentioning
confidence: 99%
“…934,973 It reduces intercalation of Hb into the lipidic bilayer and displacement of heme. 974 The presence of cholesterol in the formulation also prevents redistribution of cholesterol from RBC membranes to the liposome membrane, a process which renders RBCs osmotically fragile. 975 Small amounts of negatively charged phospholipids, such as PA, PE, dicetyl phosphate, dimyristoylphosphatidylglycerol, phosphatidylserine, phosphatidyl inositol, and PEG-PE 4.106d, have often been added to increase surface charge and inhibit liposome aggregation and fusion during storage.…”
Section: Phospholipids and Liposome Formulationmentioning
confidence: 99%
“…Such interactions result in a rapid uptake of LEH by the RES, and toxic effects manifested as vasoconstriction, pulmonary hypertension, dyspnea, etc. Anionic phospholipids also enhance the rate of hemoglobin oxidation and displace heme relative to globin [30]. It is possible to partially reduce the toxicity of anionic phospholipids by PEG modification of LEH surface [18].…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro demonstration of HbV resistance to PLA 2 enzymatic lipolysis might support the notion that the HbV is also more resistant to PLA 2 in the brain and shows a lower rate of degradation than RBC. Moreover, it has been reported that DPPC, which comprises saturated acyl chains, is less subject to lipid peroxidation than the unsaturated phospholipids in biomembranes 43, 44…”
Section: Discussionmentioning
confidence: 99%